TEACHING ENGLISH: SOCIO-CULTURAL ASPECT - Beshlei, Olga (Видавничий дім “РОДОВІД”, 2020)
The purpose of the study guide is to deepen, expand and consolidate the knowledge, abilities and skills of the students of the educational level "Bachelor" in the speciality 014 - Secondary education based on a comprehensive approach to the organization and conduct of the educational process at school. The material is presented in accordance with seven lecture sessions, which allow to consider and analyze the theoretical foundations, directions and perspectives of the educational work of the English language teacher within the framework of the educational discipline "Methodology of the formation of educational activities in a foreign language", as well as to increase the general and professional level of English language proficiency in the field methods of teaching foreign languages. The proposed practical tasks are aimed at mastering the technique of organizing the educational process, using innovative methods and technologies for educating students, and forming a stable interest in students in creative pedagogical activities. The study guide is intended for students of the faculty of foreign languages, teachers and pedagogical workers.
ELT